Thermal stability and FT-IR analysis of Phosphonium-based deep eutectic solvents with different hydrogen bond donors - Ghaedi, H. (Elsevier B.V., 2017)
Recently, deep eutectic solvent (DES), a relatively new type of solvent, has received a considerable amount of attention from researchers in different fields of research. DESs have a high potential to be an alternative to ionic liquids (ILs) and traditional solvents. It is important the knowledge of thermal stability and interaction of functional groups on both salt as a hydrogen bond acceptor (HBA) and hydrogen bond donor (HBD) in order to use of DESs as alternative solvents for numerous industrial applications. In this work, four DESs have been selected with the same salt but four different HBDs. Salt was allyltriphenyl phosphonium bromide (ATPPB) and HBDs were glycerol (GL), ethylene glycol (EG), diethylene glycol (DEG) and triethylene glycol (TEG). DESs were prepared easily into the same molar ratio of 1:4 salt to HBDs. Fourier transform infrared spectroscopy (FT-IR) as an effective technique was conducted to gain information about hydrogen-bonding and vibration modes as well as investigate the functional groups of DESs. Finally, the thermal stability of DESs was studied under nitrogen at a temperature range of 30 to 800 °C. © 2017 Elsevier B.V.